FEATURES OF USING GAME TECHNOLOGIES IN TEACHING THE RUSSIAN LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article considers the game as one of the most fascinating methods in learning the Russian language. It is noted that the features of the game in high school age are the focus on self-affirmation in front of society, the desire for practical jokes, and the focus on speech activity. It is proved that games are aimed Atmore effective and entertaining learning of the Russian language, and the use of games in lessons facilitates the acquisition of knowledge, skills and abilities, contributes to their actualization, as a result of which language learning occurs in an entertaining way that promotes rapid mastery of speech in a non-native language.